Mechanically Activated Solid-State Synthesis of Phenylhydrazone Derivatives via High-Speed Ball Milling - Zhu, Xingyi; Chen, Yuanyuan; Chen, Yuhe; Wang, Jue; Su, Weike (Letters in Organic Chemistry, 2014)
A series of phenylhydrazone derivatives was synthesized from arenediazonium tetrafluoroborates and active methylene compounds under high-speed ball milling. The reaction occurred in the absence of the solvent and products were obtained in good yield within short reaction times (no more than 30 min).
Keywords: active methylene compounds